Les musiques du français parlé Essais sur l'accentuation, la métrique, le rythme, le phrasé prosodique et l'intonation du français contemporain - Di Cristo, Albert (De Gruyter, 2016)
This volume presents a series of critical essays on the accentuation, rhythm, and intonation of contemporary French which offer new insight into the formal and functional characteristics of French prosody from three different perspectives (historical, epistemological, descriptive). These properties are interpreted in the context of the latest research into the prosody of languages.